PELATIHAN TPACK 4C UNTUK PENINGKATKAN PEMBELAJARAN ABAD 21 DI SMK N 3 TONDANO - Mahendra, I Gede Budi; Tinambunan, Medi Hermanto; Kembuan, Djubir R.E. (Jurnal Abdi Insani, 2025)
This community service activity was carried out at SMK Negeri 3 Tondano with the aim of improving teacher competency in designing and implementing TPACK-based learning and 21st-century skills through the 4C approach, namely communication, collaboration, critical thinking, and creativity. The implementation methods included socialization, training, lesson plan development workshops, microteaching, and classroom implementation. Evaluation was carried out through pre-tests and post-tests, observations, and interviews with teachers and students. The training results showed a significant increase in teacher understanding, with the average score increasing from 62.3 to 83.7 with an N-Gain of 0.58. In more detail, TPACK understanding increased from 61.2 to 83.5, 4C implementation from 63.4 to 85.2, HOTS integration from 60.1 to 81.7, and ICT utilization from 64.6 to 86.4. At the microteaching stage, 70% of teachers were able to communicate effectively, 65% facilitated collaborative discussions, and 55% used digital media well. Classroom implementation also had a positive impact on students, with 85 percent finding learning more engaging and 78 percent more motivated. Thus, this training has been proven to improve teacher professionalism while creating a more interactive, collaborative, and relevant learning experience for the needs of the 21st century. This activity recommends continued mentoring, the establishment of a forum for sharing good practices, revisions to suboptimal lesson plans, and digital infrastructure support to strengthen the ongoing implementation of TPACK and 4C.